Relevance of Low Inflation in the Southeastern European Countries - Slobodan Lakić; Damir Šehović; Mimo Drašković (Journal of Central Banking Theory and Practice, 2016)
The paper starts from the assumption that the significant reduction of the inflation problem is a result of the long-term dynamics of economic growth in countries with developing markets and, as a result, operational inability of multinational companies to increase accumulation through the policy of raising prices by creating space for their full expansion. We believe that in such circumstances civil theories on the causes of inflation are dominantly of class character. We check negative repercussions of low inflation on the examples of the countries of South-East Europe, in the regimes with fixed and flexible exchange rates, and with different strategies of monetary policy. We conclude that destructive implications of the financial crisis and psychological factors have a negative impact on a sustainable low-inflation environment, regardless of the monetary-exchange regime. We propose that low and stable inflation rates can be followed by a series of negative implications for the overall economic system, which our analysis of the observed countries proves.
Keywords: E52; E61; E62; 330; inflation/deflation; aggregate demand; monetary and fiscal policy; exchange rate/inflation rate targeting.